Analysis Of The Community Satisfaction Index On Public Services At The Sub-District Head Office Of The Ulu Musi Sub-District, Empat Lawang District - Lindayanti Lindayanti; Yun Fitriano; Yudi Irawan Abi (Journal of Indonesian Management, 2023)
The research was conducted in Ulumusi District, Empat Lawang Regency. The purpose of this study was to determine the analysis of the community satisfaction index on public services at the Sub-District Office of Ulu Musi District, Empat Lawang Regency. The data analysis technique used is to use the measurement of the value of the Community Satisfaction Index / IKM based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning the Regulation of the Minister of Administrative Reform and Bureaucratic Reform on Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units. The sample used was 210 people who came to the Ulu Musi Sub-District Office, Empat Lawang Regency. From the results of the study, it was found that the services of the Ulu Musi Sub-District Office of Empat Lawang Regency were at a good level. This is indicated by the value of the Community Satisfaction Index (IKM) of 9 (nine) IKM elements of 3.13 and with an IKM conversion value of 78.25. . The indicator that has the highest IKM value is the cost/tariff with an IKM value of 3.54 with an IKM conversion value of 88.69. While the indicator that has the lowest IKM value is the facilities and infrastructure indicator, getting an IKM value of 2.90 and an IKM conversion value of 72.64. The nine elements of the IKM at the Ulu Musi Sub-District Office, Empat Lawang Regency, the quality of service obtained after the research is all predicated on at least "Good". The weighted NR value after conducting research amounted to 3.13. So the weighted IKM value is predicated on "Good".